Assessment of effects of the genetic polymorphisms on soccer athletes - Menezes, W. C. F.; Gingozac, T. C. V.; Oliveira, L. A. S.; Pedrino, G. R.; Ternes, Y. M. F.; Santos, R. S.; Reis, A. A. S. (Genetics and Molecular Research, 2019)
Several genes have been identified as important in athletic performance. The angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism has been related to improvements in performance and exercise duration. However, there are large divergences among studies on the influence of ACE I/D polymorphism on physical performance. Other studies have demonstrated that strenuous exercise generally overloads the endogenous antioxidant system`s capacity, leading to oxidative damage to muscles and other tissues in athletes. Few studies have reported significant associations between glutathione S-transferase (GST) deletion polymorphisms and resistance performance in athletes. We examined the effects of ACE I/D and GST deletion polymorphisms in young soccer players in central Brazil. We included 65 soccer players from under-20 (18 to 20 years old) soccer teams and 60 non-athletes in a case-control study. All subjects had their physical performance investigated through the Running-based Anaerobic Sprint Test (RAST). Genotyping was performed using real-time PCR. We found that the I/D genotype was significantly more frequent in athletes compared with the non-athletes. Individuals with the ID and DD genotypes had an approximately 3.13-fold and 4.37-fold increase in strength and power-orientated performance, respectively. The DD genotype in athletes presented RAST-test results considered as excellent to good when compared with non-athletes. When we examined a possible association of the GST deletion polymorphisms and RAST test, we found no influence on athletic performance. We did find association between ACE I/D polymorphism and athletic performance. However, there was no association between GST polymorphisms and risk of oxidative damage in the muscles. Our findings may help to select young players with the most favorable genetic potential to succeed as soccer athletes.